2010
DOI: 10.1021/jp100963e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Two-Photon Absorbing Acceptor-π-Acceptor Polymethine Dyes

Abstract: We present an experimental and theoretical investigation of the linear and nonlinear optical properties of a series of acceptor-pi-acceptor symmetrical anionic polymethine dyes with diethylamino-coumarin-dioxaborine terminal groups and different conjugation lengths. Two-photon absorption (2PA) cross sections (delta(2PA)) are enhanced with an increase of pi-conjugation length in the investigated series of dyes. 2PA spectra for all dyes consist of two well-separated bands. The first band, located within the tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 39 publications
(84 reference statements)
6
60
0
Order By: Relevance
“…As an illustration, the absorption spectra of dyes 4 derivatives of aminocoumarine synthesized by A.O. Gerasev et al [83][84][85][86][87] are presented in Figure 1b.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration, the absorption spectra of dyes 4 derivatives of aminocoumarine synthesized by A.O. Gerasev et al [83][84][85][86][87] are presented in Figure 1b.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Gerasev et al [155][156][157] for the anionic polymethine dyes 4. Combined quantum-chemical and spectral studies of the dyes 4 [85][86][87] have shown that two lowest electron transitions are split transitions, involving two low positioned acceptor levels, in contrast to the cationic cyanine dyes where two lowest transitions are connected with two split donor levels.…”
Section: Introduction Of π π π π-Donor Substituents To Terminal Groupsmentioning
confidence: 99%
“…Difluoroboron compounds have wide range applications in sensors, optoelectronic devices, probes, and catalysis in the past few years [3][4][5][6]. Herein, we report the crystal structure of difluoroboron 3-(2,2,2-trifluoroacetyl)chroman-4-one.…”
Section: Commentmentioning
confidence: 99%
“…The positions 5 and 7 when substituted with a donor moiety such as -OH, −NEt 2 , −NH 2 and -OCH 3 and the positions 3 and 4 substituted with acceptors like -CN, −COOEt and benzazolyl group, the coumarin fluorophore experiences a red shifted absorption and hence red shifted emission. Increasing the rigidity of the donor [46] and acceptor [47] groups also adds to the red shift of the coumarin molecules. The substitution at 4-position by -CN group (an acceptor) induces a red shift in the emission of coumarins [44].…”
Section: Introductionmentioning
confidence: 99%